Research progress on the role and mechanism of the glymphatic system in the occurrence and development of brain diseases - CHANG Junlei; FENG Ziying (Guangxi Yike Daxue xuebao)
Biomedical research in recent years has revealed a new mechanism by which the brain can effectively remove metabolic waste generated by the neural tissue through the glymphatic system. This system efficiently promotes the exchange of cerebrospinal fluid and brain interstitial fluid, which is similar to the peripheral lymphatic system. It plays a role in removing metabolic waste in the brain and is essential to maintain the homeostasis of the brain microenvironment. An increasing number of studies have found that the function of the glymphatic system is impaired under conditions of various brain diseases, which is likely a key promoting factor in the occurrence, formulation and development of various brain diseases. Therefore, understanding the role of the glymphatic system and the underlying mechanism in brain diseases is of great significance for developing new targeted therapeutic strategies.